2013
DOI: 10.1016/j.rpor.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and survival in metastatic breast cancer: A single institution experience

Abstract: Many of the prognostic factors in metastatic breast cancer found in our study are known in the literature but some of them, like the application of locoregional treatment (radiotherapy or surgery) and the use of bisphosphonates, need to be further investigated in randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 33 publications
6
30
3
2
Order By: Relevance
“…[4][5][6] In our patient population, overall survival after the diagnosis of liver metastases was 18 months which was in line with the results of more recent studies. 12 We revealed that early stage disease at diagnosis, non TNBC disease and presence of local hepatic treatment were long survival after hepatic metastasis by multivariate analysis (Table 4). However age at diagnosis, adjuvant chemotherapy, and adjuvant endocrine therapy were found to have no influence on survival in patients after the development of hepatic metastases.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[4][5][6] In our patient population, overall survival after the diagnosis of liver metastases was 18 months which was in line with the results of more recent studies. 12 We revealed that early stage disease at diagnosis, non TNBC disease and presence of local hepatic treatment were long survival after hepatic metastasis by multivariate analysis (Table 4). However age at diagnosis, adjuvant chemotherapy, and adjuvant endocrine therapy were found to have no influence on survival in patients after the development of hepatic metastases.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that nearly 30% of breast cancer patients will develop liver metastases along the duration of their disease. 1-2 Liver metastases usually develop in the terminal stage of breast Hepatic with brain 13 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) International Journal of Hematology and Oncology cancer, and are often accompanied by extrahepatic metastases. Isolated liver metastases are very rare (4%-5%).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment modalities have extended from mastectomy to breast conservation therapy. Adjuvant radiotherapy has shown long term survival benefit in these patients [1,4,5,6,7]. Post mastectomy radiotherapy has a limited role in patients with four or more metastatic axillary nodes, large primary tumours and chest wall invasion [4].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer, one of the most prevalent cancers through the world, is the main cause of cancer death among the women (1). According to recent studies about 40% of all breast cancer patients are at high risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%